Finding meaning in business: theology, ethics, and vocation - Okonkwo, Bartholomew C. (Palgrave Macmillan, 2013)
Contents List of Illustrations Preface Acknowledgments Introduction PART ONE: BUSINESS AND CALLING Giving Meaning to Work: The Spiritual Challenge of Our Time Ingeborg Gabriel Reclaiming the Concept of Calling Hans Dirk van Hoogstraten The Entrepreneurial Vocation: Is Creating Wealth a Calling? Georges Enderle The Evolution of Business as a Christian Calling Gary L. Chamberlain PART TWO: FOSTERING A COMMUNITY OF WORK Toward a Theology of Business Denise Daniels Fusion, Fission, or Vision: One Calling, Three Metaphors John Strain and John Sherrington The Enterprise as Community of Persons: The Case of Bimbo Group Patricia Debeljuh PART THREE: FORMATION OF BUSINESS LEADERS Questions Organizational Leaders Pose to Theologians Andre Delbecq Roman Catholic and Protestant Perspectives on Business as a Calling: Managerial Leadership in the Corporate Sphere Shirley Roels and Regina Wentzel Wolfe Toward an Experience Training: A Perspective from Lonergan Maria Soledad Martinez Kasten, translated by Bartholomew C. Okonkwo Pedagogical Models and Practice Jack Ruhe and Ron Nahser Bibliography Notes on Contributors Index